Association of obesity with orbital fat expansion in thyroid eye disease - Po-Chin Kuo; Shu-Chun Kuo; Yi-Shan Teng; Chun-Chieh Lai (BMC Ophthalmology)
Abstract Background To investigate the association between obesity and orbital fat expansion in proptosis of thyroid eye disease. Methods This observational study retrospectively enrolled 87 participants who received orbital fat decompression surgery for thyroid eye disease. Primary outcome measures included average body mass index (BMI) and the proportion of the study sample with overweight and obesity, compared with the general Taiwanese population. Secondary outcome measures included the association of obesity with proptosis severity, removed fat volume, and thyroid status. Results The average BMI (25.59 ± 4.36 kg/m2) of the study sample was significantly higher than that in the general population of Taiwan (24.5 kg/m2; P = 0.012). Participants with overweight (19.52 ± 3.52 mm) and obesity (21.25 ± 3.76 mm) exhibited significantly more severe proptosis than participants without overweight (18.05 ± 3.37 mm) and without obesity (18.09 ± 3.02 mm; P = 0.029 and P < 0.001, respectively). In addition, a significantly greater orbital fat volume was removed from the group with obesity (4.61 ± 1.17 ml) versus that without obesity (3.57 ± 1.12 ml; P = 0.021). A positive correlation between BMI and removed fat volume was noted (correlation coefficient = 0.291, P = 0.005). BMI was an independent factor predicting both proptosis severity (P < 0.001) and removed orbital fat volume (P = 0.02). Conclusions Obesity is associated with orbital fat expansion and consequently more severe proptosis in thyroid eye disease. Weight control may be a potential strategy to prevent thyroid-associated exophthalmos.